Synergy of Virtual Reality With English Learning in Elementary School Students in the Cipanas District - Dwi Jatmika, Rahmat Taufiq; Kurniawati, Nia; Handayani, Trini; Amalia, Mia; Sugiarni, Rani (Amala Jurnal Pengabdian Kepada Masyarakat, 2022)
Virtual Reality is a tool to provide real visualization that its users can see. Virtual Reality can also be a learning tool requiring clear visuals. Bringing those far away is one of the functions of this VR. With VR, learning methods are increasingly realized clearly with presentations that can be seen immediately. Users do not need to go directly into the field to see the original visualization, but users can see directly with virtual vision. English learning can be presented with the help of VR, where children and teachers can visually see colours, animate and inanimate objects, and visualizations. This service has five stages: problem identification, information processing and offered solutions, training material preparation, training implementation, and evaluation. From these five approaches, teachers as learning intermediaries in elementary schools need to improve learning methods and modules. In contrast, with the rapid advancement of technology, teachers need to be role models of learning for their students.